2015
DOI: 10.1136/bmjopen-2015-008576
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring adverse events in Norwegian hospitals from 2010 to 2013

Abstract: ObjectivesTo describe how adverse event (AE) rates were monitored and estimated nationally across all Norwegian hospitals from 2010 to 2013, and how they developed during the monitoring period. Monitoring was based on medical record review with Global Trigger Tool (GTT).SettingAll publicly and privately owned hospitals were mandated to review randomly selected medical records to monitor AE rates. The initiative was part of the Norwegian patient safety campaign, launched by the Norwegian Ministry of Health and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 11 publications
0
50
0
3
Order By: Relevance
“…Other studies have presented results for regions and healthcare systems, 14 30 31 as well as subgroups at national level. 23 International comparisons of levels of patient safety are of great interest as a means to study organisational development in healthcare.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have presented results for regions and healthcare systems, 14 30 31 as well as subgroups at national level. 23 International comparisons of levels of patient safety are of great interest as a means to study organisational development in healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…14 The category F-I had previously been used in the American study of AEs among Medicare beneficiaries. 23 Both compounded categories were applied in the comparison of Norwegian and Swedish AE rates.…”
Section: Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2010, all hospitals in Norway are required to review a minimum of 20 randomly selected medical records per month using the IHI GTT method [11]. Nordland Hospital Trust chose from the start to review 140 records monthly to achieve more accurate measurement and better support for local improvement initiatives [12].…”
Section: Study Populationmentioning
confidence: 99%
“…Several international studies have shown that adverse events occur in nearly 10% of hospital admissions, and of these, 40%‐50% could have been prevented . In Norway, adverse events occur in 7%‐8% of admissions . Few studies have investigated adverse events in maternity units, but 1 study in Spain showed that adverse events were experienced by 3.6% of pregnant women admitted to a hospital …”
Section: Introductionmentioning
confidence: 99%